PENGARUH REVEALED COMPARATIVE ADVANTAGE, LUAS LAHAN, NILAI TUKAR, INFLASI, DAN PERTUMBUHAN EKONOMI TERHADAP EKSPOR KOPI DI BERBAGAI NEGARA - Shabri, Muhammad Ivan; Saputra, Putu Mahardika Adi (Contemporary Studies in Economic, Finance and Banking, 2023)
The purpose of this study is to determine how the influence of revealed comparative advantage, land area, exchange rate and economic growth on coffee exports of 4 world countries in 2010-2020.  This study used a quantitative research approach. The results of the study said that each variable, namely revealed comparative advantage, land area, exchange rate and economic growth on coffee exports of 4 world countries in 2010-2020 had a significant influence.  With an expansion in land area, it can increase the amount of coffee that can be harvested and produced so that it can affect a country's export performance. The occurrence of exchange rates cannot be separated from the deappreciation or appreciation of each exchange rate in each country. With a decrease in the exchange rate, it can affect community or government activities in carrying out activities in the form of exports.  The value of coffee exports we see the superiority of the commodity by measuring its comparative index owned by the country, it will be compared. Economic growth can be determined due to an increase in goods and services produced by a country. So that the demand for certain goods increases and will affect the exports of a particular country. Inflation can occur due to high public consumption, excess market liquidity that triggers speculation and distribution of goods that are not smooth.